Immunogenicity and duration of immunity of the polyvalent vaccine against chicken salmonellosis - SenО. М.; SaliyО. О.; Mazurkevych, V. I.; Sobko, Y. A. (Regulatory Mechanisms in Biosystems, 2020)
Poultry salmonellosis causes serious economic damage and must be prevented by disinfection, zoohygienic measures or by vaccination. To develop a new polyvalent vaccine against poultry salmonellosis, we used bacterial strains of Salmonella enteritidis, S. typhimurium and S. gallinarum. Antigenic and immunogenic efficacy of the vaccine was tested on specific-pathogen free chickens, which were divided into five groups of 10 birds in each group and were vaccinated intramuscularly at 8 and 12 weeks: group A (non-immunized control), group B (S. enteritidis mono-vaccine), group C (S. typhimurium mono-vaccine), group D (S. gallinarum mono-vaccine) and group E (trivalent vaccine Polimun Salmo). None of the immunized birds showed such adverse reactions as abnormal behaviour, mortality or signs of anorexia, depression or diarrhea. Two weeks after the revaccination, 5 birds in each group were challenged by watering 3 cm3 of working suspensions of S. gallinarum, S. typhimurium and S. enteritidis control strains at a concentration of 1 × 109 CFU. 72 h after the challenge, faeces were collected from all chickens in each group to identify Salmonella excretion with faeces, and the chickens were euthanized. Significant protection against the virulent challenge was observed in all immunized groups based on mortality and post-mortem lesions compared with the non-immunized control group. Blood samples were selected weekly from 5 chickens of each group for 184 days. The antigenic efficacy of the vaccines was studied by reaction of haemagglutination in the obtained serum. The potent antigen-specific response to lymphocyte activation found in all immunized groups indicated the induction of immune responses. Overall, the results showed that persistent immunity is formed in 4 weeks after the revaccination and lasts for a productive period. Immune response of chickens on day 184 after vaccination with Polimun Salmo was 1: 647, indicating that the developed polyvalent vaccine against common serovars of S. enterica in poultry is effective and immunogenic and can be further used in field studies.